Business for the common good : a Christian vision for the marketplace - Wong, Kenman L., 1964-; Rae, Scott B. (Downers Grove, Ill. : IVP Academic, 2011)
Is business just a way to make money? Or can the marketplace be a venue for service to others? Scott B. Rae and Kenman L. Wong seek to explore this and other critical business issues from a uniquely Christian perspective, offering up a vision for work and service that is theologically grounded and practically oriented.
Your work is an altar -- The shape of a calling to business -- Business and spiritual formation -- Wealth, success and ambition -- Business and the global economy -- Ethics in the workplace -- Leadership and management: serving employees -- Marketing: serving customers -- Stewardship and sustainability: serving the garden and our neighbors -- Emerging directions in business.
Includes bibliographical references and indexes.
Keywords: Business -- Religious aspects -- Christianity; Business ethics; Social responsibility of business